2009
DOI: 10.1128/jvi.00422-09
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases Modulate Entry of Ebola Virus and Vesicular Stomatitis Virus Pseudotyped Vectors

Abstract: To explore mechanisms of entry for Ebola virus (EBOV) glycoprotein (GP) pseudotyped virions, we used comparative gene analysis to identify genes whose expression correlated with viral transduction. Candidate genes were identified by using EBOV GP pseudotyped virions to transduce human tumor cell lines that had previously been characterized by cDNA microarray. Transduction profiles for each of these cell lines were generated, and a significant positive correlation was observed between RhoC expression and permis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 45 publications
(52 reference statements)
3
76
0
Order By: Relevance
“…Our results suggest that filamentous influenza virus utilizes macropinocytosis as its cellular entry pathway similarly to other filamentous viruses, such as Ebola virus (33,41,47). This is especially interesting given the observation that primary human isolates of influenza virus, as well as the recent 2009 pandemic strain, appear to be predominantly filamentous (11,24,34), suggesting that macropinocytosis may be the dominant entry pathway for most strains of influenza virus.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results suggest that filamentous influenza virus utilizes macropinocytosis as its cellular entry pathway similarly to other filamentous viruses, such as Ebola virus (33,41,47). This is especially interesting given the observation that primary human isolates of influenza virus, as well as the recent 2009 pandemic strain, appear to be predominantly filamentous (11,24,34), suggesting that macropinocytosis may be the dominant entry pathway for most strains of influenza virus.…”
Section: Discussionmentioning
confidence: 74%
“…This is especially interesting given the observation that primary human isolates of influenza virus, as well as the recent 2009 pandemic strain, appear to be predominantly filamentous (11,24,34), suggesting that macropinocytosis may be the dominant entry pathway for most strains of influenza virus. As a result, pharmaceutical inhibitors of virally induced macropinocytosis may prove to be a valuable antiviral treatment, effective against multiple different viruses, including, among others, influenza virus, Ebola virus, vaccinia virus, and Nipah virus (30,33,38,41,47), as reviewed in reference 31. Taken together, our results show that the main entry pathway for filamentous influenza virions is macropinocytosis, whereas the spherical forms of influenza virus are capable of entering cells through either macropinocytosis or clathrin-mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed that clathrincoated pits are indeed utilized by infectious EBOV to enter permissive cells (6). It has also been speculated that, because of their large size, filoviruses may utilize macropinocytosis to enter permissive cells (19,56). Recently, the latter mechanism of entry was demonstrated experimentally for the first time for a filovirus (51,57).…”
mentioning
confidence: 60%
“…Since prenylation of Rab GTPases is dependent on GGTase II, which is not affected by the inhibitor GGTI-286, the main focus of the present study was the Rho GTPase family. These are key regulators of the cell cytoskeleton, cell cycle, gene expression, and vesicle trafficking (19,51) and are involved in the entry of diverse viruses into the host cell (14,42,48,52) but also in viral morphogenesis (27,61), infection spreading (12), or virus-induced cell motility (61,66). In this regard, a general inhibition of Rho GTPase-mediated signaling could affect simultaneously diverse and relevant cellular processes that may explain the abnormal viral factory size and extensive accumulation of envelope precursors and immature virions observed when ASFV infection takes place under these conditions.…”
Section: Discussionmentioning
confidence: 99%